Role of Pseudomonas Flourescens on Lead Phytoremediation and Recovery of Adverse Effects in Sansevieria Roxburghiana Plant under Hydroponic Studies - Ramesh, Thanusree Mallakuntla; Gurajala, Hanumanth Kumar; Mopati, Rupadevi; Kathera, Chandrasekhar; Jasti, Pramodakumari (International Journal of Scientific Research in Biological Sciences, 2019)
Phytoremediative potential of Sansevieria roxburghianawas studied in association with siderophore producing bacteria Pseudomonas flourescens in synthetic medium supplemented with different concentrations of lead (40, 80, 120 and 160 mg/L)over aperiod of 30 daysalong with control.Thechlorophyll content decreasedindicatingincreased production of reactive oxygen species effecting photosynthetic activity, this was confirmed by increased malondialdehyde content. The highest concentrations of Pb 6.1 mg g-1 and 26.4 mg g–1 were accumulated in shoots and roots of S.roxburghianagrown on Pb-rich synthetic medium inoculated with Pseudomonas flourescenscompared with uninoculated plants4.2 mg g–1 and 20.23 mg g–1. In S.roxburghianabioconcentration factor (BCF) increased with increase in lead concentration (P<0.05) beforePseudomonas flourescensinoculation and after inoculation BCF showed increase upto 160mg/L and reduced upon increasing concentration of metal.Decrease in biomass with increase in Pd concentration at 40 mg and 80 mgis observed and decreased gradually. Translocation factor (TF) increased at 40 mg, 80 mg but not at 120 mg, 160 mg concentrations without Pseudomonas flourescens and is also not significant with addition of Pseudomonas at all concentrations.The tolerance index showed increase at 40,80 concentrations and low at 120,160 mg concentrations even with inoculation of Pseudomonas flourescens. From the results it is revealed that theS.roxburghianaalong with Pseudomonas flourescens can contribute for more accumulation and high degradative potential towards lead.